2022
DOI: 10.1155/2022/5105545
|View full text |Cite
|
Sign up to set email alerts
|

Wu-Teng-Gao External Treatment Improves Th17/Treg Balance in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) represents the consequence of an immune response of the body’s immune system attacking healthy cells. This chronic inflammatory disorder has complicated pathogenesis. Traditional Chinese medicine (TCM) is well recognized as an effective therapy in treating RA and has been widely applied for centuries. Wu-Teng-Gao (WTG) is used as a representative natural herb formula in RA treatment in China, while its mechanisms are to be fully clarified. The present study attempted to explore mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…An increase in Foxp3 expression and a decrease in Ror-γt expression were observed. In addition, a decrease in pro-in ammatory cytokines (IL-1, IL-6, TNF-α, IL-17) and an increase in anti-in ammatory cytokines (IL-10 and TGF-β) were observed, and it was found that bone damage was inhibited in histological staining [22]. In a study conducted in a lupus mouse model, the effect of Cucurbitacin IIb on Th17 and Treg cell percentages, Foxp3 and Ror-γt expression levels in cells isolated from the spleen of mice was investigated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An increase in Foxp3 expression and a decrease in Ror-γt expression were observed. In addition, a decrease in pro-in ammatory cytokines (IL-1, IL-6, TNF-α, IL-17) and an increase in anti-in ammatory cytokines (IL-10 and TGF-β) were observed, and it was found that bone damage was inhibited in histological staining [22]. In a study conducted in a lupus mouse model, the effect of Cucurbitacin IIb on Th17 and Treg cell percentages, Foxp3 and Ror-γt expression levels in cells isolated from the spleen of mice was investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Th17/Treg ratio in our study were found to be lower in RA group compared to the HC group. This maybe because CD4 + Ror-γt + cells were investigated as Th17 in our study and in many other studies investigating Treg and Th17, CD4 + IL-17A + Th17 cells were studied [42,22]. We aimed to investigate the effects of BA and CaF on CD4 + Foxp3 + cells and CD4 + Ror-γt + cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Yao et al. ( 238 ) performed animal experiments and showed that the external application of Wuteng ointment greatly inhibited the expression levels of inflammatory cytokines IL-17, TNF-α, IL-1, IL-6, and RNAKL, and improved the expression of anti-inflammatory cytokines IL-10 and TGF. Through further experiments, it was found that different doses of Wuteng ointment significantly reduced the ROR-γt level in spleen tissue, increased the Foxp3 level, altered the Th17/Treg cell ratio, improved the Th17/Treg cell imbalance in CIA rats, inhibited bone destruction, and played an effective therapeutic role in RA.…”
Section: Immunotherapy For Rheumatoid Arthritis and Postmenopausal Os...mentioning
confidence: 99%
“…In reports (237), Chinese medicine application technology has been recognised by patients because of its advantages in reducing toxic damage to the gastrointestinal tract, liver, kidney, and other organs, its convenient use, and its therapeutic effects in RA. For example, Yao et al (238) performed animal experiments and showed that the external application of Wuteng ointment greatly inhibited the expression levels of inflammatory cytokines IL-17, TNF-a, IL-1, IL-6, and RNAKL, and improved the expression of antiinflammatory cytokines IL-10 and TGF. Through further experiments, it was found that different doses of Wuteng ointment significantly reduced the ROR-gt level in spleen tissue, increased the Foxp3 level, altered the Th17/Treg cell ratio, Based on the above research, we can conclude that both Western medicine and traditional Chinese medicine.…”
Section: Reduced Immune Inflammatory Factorsmentioning
confidence: 99%